Analysis of Fifth Graders’ Higher Order Thinking Skills in Studying Human and Animal Respiratory Organs - Ika Maryani; Rifky Hanifah; Siwi Purwanti; Rafael Onate (Profesi Pendidikan Dasar, 2021)
Background: Higher order thinking skills (HOTS) are crucial for students to face the 21st century development. This study aimed to determine higher order thinking skills of the fifth graders at Muhammadiyah elementary school in Demangan and Baitussalam II Islamic elementary school in solving questions on human and animal respiratory organs.Method: A descriptive quantitative approach was employed. It included survey and ex-post factor designs. The research data were collected using tests.Result: The participants of the study achieved medium scores on three categories of HOTS. Thirty nine percent of Ibnu Thufail fifth graders achieved a medium score on judgement and critical thinking, 48% of Ibnu Rusdy fifth graders obtained a medium score on similar category, and 42% of the Muhammadiyah fifth graders got low scores on judgement and critical thinking. Meanwhile in problem-solving, 43% students were in medium category, 39% in low category, and 32% in medium category. Forty eight percent of the students obtained medium scores and 52% achieved poor scores.Implications: The research findings imply that students’ HOTS in natural science need to be improved. Novelty: The present study revealed students’ HOTS based on judgment and critical thinking, problem solving, logic and reasoning skills.